2008
DOI: 10.1016/j.bbamem.2008.03.021
|View full text |Cite
|
Sign up to set email alerts
|

Current perspectives in pulmonary surfactant — Inhibition, enhancement and evaluation

Abstract: Pulmonary surfactant (PS) is a complicated mixture of approximately 90% lipids and 10% proteins. It plays an important role in maintaining normal respiratory mechanics by reducing alveolar surface tension to near-zero values. Supplementing exogenous surfactant to newborns suffering from respiratory distress syndrome (RDS), a leading cause of perinatal mortality, has completely altered neonatal care in industrialized countries. Surfactant therapy has also been applied to the acute respiratory distress syndrome … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

21
654
2
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 470 publications
(683 citation statements)
references
References 374 publications
21
654
2
2
Order By: Relevance
“…Deficiency of LS in the alveoli, or an imbalance of its chemical composition, induces a number of pathological conditions (8). For instance, neonatal respiratory distress syndrome affects prematurely born infants when LS is not yet matured or is completely lacking; this deficiency may be lethal if left untreated.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Deficiency of LS in the alveoli, or an imbalance of its chemical composition, induces a number of pathological conditions (8). For instance, neonatal respiratory distress syndrome affects prematurely born infants when LS is not yet matured or is completely lacking; this deficiency may be lethal if left untreated.…”
mentioning
confidence: 99%
“…In these cases, the most common treatment is intratracheal administration of an exogenous LS into the lungs (9). In case of acute respiratory distress syndrome the mortality is 35 to 45% (10) and an effective treatment is clearly lacking (8). An accurate characterization of the molecular structure and dynamics of endogenous and exogenous lung surfactant, together with relating such molecular properties with LS functions, should aid significantly in the development of more efficient treatments.…”
mentioning
confidence: 99%
“…18,33 Consequently, a physiological level of cholesterol helps solidify the PS membranes, but a supraphysiological level of cholesterol deteriorates the biophysical function of PS by fluidizing the surfactant vesicles and films. 18,33 Figure 1b shows the self-assembled PS ultrastructure with the addition of three membrane-binding surfactant proteins, such as SP-B, SP-C, and SP-A (the dynamic process of PS selfassembly can be found in Video S2 of the Supporting Information). It is found that all three proteins promote fusion of the unilamellar micelles into larger multilamellar micelles, in good agreement with experimental observations of the ultrastructure of protein-containing natural PS.…”
Section: Resultsmentioning
confidence: 99%
“…15−17 The PS is composed of approximately 90% lipids, including various phospholipids and cholesterol, and 10% proteins (named SP-A, SP-B, SP-C, and SP-D) by weight. 18 Among these four surfactant-associated proteins, SP-B and SP-C are small hydrophobic membrane proteins that are essentially important for reducing alveolar surface tensions and thus indispensable for sustaining normal respiratory physiology. 19 SP-A and SP-D are large hydrophilic proteins and members of the collectin family, which play an important role in innate host defense by binding inhaled particles and pathogens.…”
Section: U Nderstanding Interactions Between Nanoparticlesmentioning
confidence: 99%
“…Subsequently, equal volumes of DEX-NG dilutions and siRNA were mixed and incubated at 4°C for ≥ 15 min to allow complexation. protein compositions can be found in the literature [11,20,21].…”
Section: Preparation Of Cationic Dextran Nanogels and Loading With Sirnamentioning
confidence: 99%